فاعلية بعض تطبيقات السحب الحاسوبية (Computing Clouds) في تنمية مهارات إنتاج مقاطع الفيديو التعليمية لدى معلمات المرحلة الابتدائية بمدينة جدة - قاسم، سعاد فؤاد خالد (دار سمات للدراسات والأبحاث, 2017)
يهدف البحث الحالي إلي قياس فاعلية بعض تطبيقات السحب الحاسوبية (computing clouds) في تنمية مهارات إنتاج مقاطع الفيديو التعليمية لدى معلمات المرحلة الابتدائية بمدينة جدة. ولذلك اتبعت الباحثة المنهج شبه التجريبي حيث تم استخدام بعض تطبيقات السحب الحاسوبية (computing clouds) لتدريس محتوى تدريبي يضم مهارات إنتاج مقاطع الفيديو التعليمية بجانبيه المعرفي والأدائي، بالإضافة إلي الاختبار التحصيلي (قبلي وبعدي) وبطاقة تقييم منتج (قبلي وبعدي)، وتكونت عينة البحث من مجموعتين تجريبية وضابطة بلغ عددهن (50) معلمة من معلمات المرحلة الثانوية بالمدرستين ابتدائية تحفيظ القرآن الأولي ومدارس معرفة العبير الأهلية. ولاختبار صحة، الفروض تم استخدام (اختبارات لمجموعتين مستقلتين -اختبارات ت لعينة واحدة) ببرنامج معالجة الحزم الإحصائية ,SPSS16 وقد توصلت نتائج البحث إلي وجود فروق ذات دلالة إحصائية بين متوسطي درجات المجموعة التجريبية والضابطة لصالح المجموعة التجريبية. ومن هنا توصي الباحثة باستخدام تطبيقات السحب الحاسوبية (computing clouds) للمعلمات والتي تساعد على تطوير وتنمية العملية التعليمية.
The current research aims to measure the effectiveness of some computing clouds applications (computing clouds) in the developing the skills of the producing educational videos to the primary school teachers in Jeddah, therefore researcher followed the quasi-experimental approach where the use of some computing cloud applications for teaching training content including the production of educational videos of both besides cognitive and performance, in addition to the pro/pre collective test a card of pre/pro product evaluation. The research sample consisted of two groups experimental group and the control group of (50) teachers of secondary school teachers of the two schools; Al Abeer national knowledge school، and Quran first Primary school and for the test of the validity of hypotheses used (test for two independent -groups، test for one sample) in the program of processing statistical package. The research findings concluded to that there is statistically significant difference at the two averages of the experimental group and control group, hence the researcher recommends using the applications of computing clouds for the teacher, which helps them develop their educational process.
Keywords: تطبيقات السحب الحاسوبية -- مقاطع الفيديو التعليمية -- المرحلة الابتدائية -- مدينة جدة